An Experience Of An Adolescent With Non-Suicidal Self-Injury (NSSI) Behaviour: A Narrative Analysis - Nor Dzahirah Binti Adzhari
The purpose of this study is to explore the life experiences of adolescents who engage in non-suicidal self-injury (NSSI) using the Narrative analysis method. This study was done at a school in the Kuala Lipis area of the Pahang state. This research focuses on the case study design, in which just one subject is chosen to be interviewed for the analysis. Participants are picked based on referrals from the school's guidance and counseling teacher. In this study, participants are 16-year-olds who are still in form four and have engaged in NSSI behaviours. For this qualitative study, data were obtained from study participants through observation and interviews. Use coding and narrative methods to analyze data. The outcomes of the research revealed that three themes can be determined from the participant's narratives. These themes include forms, emotions, and factors that influence NSSI behaviour among adolescents. The forms of NSSI behaviour are "cutting" and "hitting." Participants used a blade and shattered glass to engage in both types of activity. The findings of the study also show that emotional wellbeings are an important factor in NSSI behaviour in adolescents. There are two emotional states: negative emotions and emotional numbness. The research also demonstrates that unfulfilled relationship factors, social media, peers, society, and family issues contribute to NSSI behaviour among adolescents. The implications for schools and researchers are also examined. For future studies, it has been recommended that researchers may conduct interviews with a greater number of participants to investigate the similarities and differences between the various forms and factors that induce NSSI activity among adolescents